A Mosque in a Thousand Temple Island: Local Wisdom of Pegayaman Muslim Village in Preserving Harmony in Bali - Mahmud Arif (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2019)
There are some scholars, such as Clifford Geertz, Geoffrey Robinson and Miquel Covarubbias who pay much attention to the patterns of the religious and cultural life of Balinese. They show various perspectives on Balinese religious and cultural lives, those that are generally closely related to Hinduism and tourism. For this reason, a study on the religious life of the Muslim communities in Bali is interesting because it represents various viewpoints while revealing another side of Balinese exoticism. Pegayaman Muslim village of Buleleng regency is an old village inhabited by Muslims amidst strong Hindu influences. This village is unique and recognized as one of the oldest Muslim villages in Bali. In general, the people in this village are able to live side by side peacefully with the adherents of other religions through local wisdom by building harmony with puri(castle), pura (temple), and Balinese customs, like actualization of Menyama Beraya in daily life and Sokok Base that are presented at procession of Maulid festival every year.